2008
DOI: 10.1088/0957-4484/19/05/055706
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of nanostructured rutile and anatase plates for improving the photosplitting of water

Abstract: Developing new semiconductor materials for improving photocatalytic reactivity is important for solving the challenging environmental and energy problems we are facing today. This work focuses on increasing the quantum efficiency in titania photocatalysts for photocatalytic (oxidation of acetaldehyde) and photosynthetic (photosplitting of water) reactions by synthesizing pure phase rutile and anatase nanostructures with well defined morphologies and investigating their photocatalytic performance compared to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 30 publications
3
28
0
1
Order By: Relevance
“…The ratio B/A defines the degree of truncation. The shape predicted by the thermodynamic theory corresponds closely to that of anatase nanoparticles synthesized under nearequilibrium conditions by the sol-gel [84] or hydrothermal routes [85], as confirmed by the high-resolution transmission electron micrograph in figure 10.5. Simulated images of anatase nanocrystals [82,83] generated by the thermodynamic model and the standard Wulff construction are contrasted in figure 10.4; only the Ti atoms are shown for clarity and to facilitate comparison with transmission electron micrographs.…”
Section: Particle Shape Calculationsupporting
confidence: 63%
“…The ratio B/A defines the degree of truncation. The shape predicted by the thermodynamic theory corresponds closely to that of anatase nanoparticles synthesized under nearequilibrium conditions by the sol-gel [84] or hydrothermal routes [85], as confirmed by the high-resolution transmission electron micrograph in figure 10.5. Simulated images of anatase nanocrystals [82,83] generated by the thermodynamic model and the standard Wulff construction are contrasted in figure 10.4; only the Ti atoms are shown for clarity and to facilitate comparison with transmission electron micrographs.…”
Section: Particle Shape Calculationsupporting
confidence: 63%
“…It can be observed that the synthesized TiO 2 powder consists of pure anatase (curve 1). The pattern of TiO 2 Degussa P25 powder (curve 3) exhibited both anatase and rutile crystalline polymorphs in a wt % ratio A: R = 88: 12 (Table 1), which is in accordance with recently reported values in the literature [14,15]. After the doping procedure, the crystalline structure of each powder was preserved (curves 2 and 4) due to the temperature of thermal treatment which was only 50 °C higher than the calcination temperature of the undoped powder and below the temperature of anatase-to-rutile phase transition.…”
Section: Characteristics Of Catalystssupporting
confidence: 90%
“…Zhang et al [26] and Anpo et al [27] have discussed about the mechanism responsible for photocatalytic activity of TiO 2 . Other than electronic and structural requirements, a number of factors such as size, morphology and surface area play a critical role in the photocatalytic efficiencies of TiO 2 [28]. Enhancement of surface area of the materials can improve the catalytic efficiency; so, it is important to develop a synthesis method for the preparation of catalysts composed of active TiO 2 species within high surface area matrix, such as porous alumina and silica.…”
Section: Introductionmentioning
confidence: 99%